Uso de geofísica en la caracterización de movimientos en masa de los taludes en ventana 3 y 4 de la Central Hidroeléctrica DELSITANISAGUA - Iñiguez Banegas, Miller Fabricio (2023)
The following research deals with the use of geophysics in the characterization of mass movements of the slopes in window 3 and 4 of the DELSITANISAGUA Hydroelectric Power Plant, the study area is located within the DELSITANISAGUA Hydroelectric Power Plant belonging to the Electrical Corporation of Ecuador CELEC EP, geographically located east of the eastern mountain range of the Andes, southeast of Ecuador, between the rural parishes of Sabanilla and El Limón in the Zamora canton, province of Zamora Chinchipe, 12 km west of the city of Zamora. Once the results were obtained regarding the superficial lithological characterization through the description of 30 outcrops along the road leading to the Window 4 sector, it was corroborated that the lithology of the sector is composed of gneiss and schist accompanied by residual soils and colluvial deposits, belonging to the Sabanilla Unit. Likewise, in the Window 3 and Window 4 areas of interest, residual and colluvial soils accompanied by loose rock blocks, detritus, sub angular gravels, coarse brown sands and sandy silts were also found. Nine electrical resistivity tomographies [ERT] were performed, which were strategically divided into 4 electrical profiles in Window 3 and 5 electrical profiles in Ventana 4. The interpretation of the electrical profiles with the correlation of the lithology of the sector, studies carried out in the area, allowing the interpretation of four geoelectric units, likewise a lithological profile was obtained estimating the landslide rupture surface, soil composition, saturation zones and phreatic levels. In the interpretation of the electrical profiles the Schlumberger device was used, being this configuration the one that provided better resolutions compared to the rest of the devices. Finally, the morphometry and area affected by the landslides were identified, resulting in a translational landslide in Window 3 with a slid mass volume of 133000.9 m3 and a rotational landslide in Window 4 with a slid mass volume of 94848.65 m3. Key words: Electrical resistivity tomography [ERT], Electrical resistivities, Rupture plane, Landslide characterization, Geophysics and Schlumberger.